2021
DOI: 10.31933/dijdbm.v2i3.824
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction Caused by Work Stress, Job Satisfaction, and Organizational Commitment to Turnover Intention on the Employees at Pt. Bali Towerindo Sentra, TBK

Abstract: This research aimed to investigate the affect which appeared on Employees at PT. Bali Towerindo Sentra Tbk relates to the high of turnover intention which caused by work stress, job satisfaction and organizational commitment. This research was included in type of causality research with quantitative research methods. Those population here was employees at PT. Bali Towerindo Sentra Tbk, which amounted to 395 people. Meanwhile, the sample consisted of 202 respondents (Slovin, 5% error tolerance). Data analysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…The results of this study differ from research that has been conducted [7], [32], [42], [60] which found a negative influence between organizational commitment and turnover intention. Different results were obtained from other studies belonging to [54], [72], [73] which showed that organizational commitment has a positive and significant effect on turnover intention. The effect of transformational leadership on turnover before being mediated was found to be insignificant with an original sample value of -.090 and p values (.216 > .05).…”
Section: Organizational Commitment To Turnover Intentioncontrasting
confidence: 76%
“…The results of this study differ from research that has been conducted [7], [32], [42], [60] which found a negative influence between organizational commitment and turnover intention. Different results were obtained from other studies belonging to [54], [72], [73] which showed that organizational commitment has a positive and significant effect on turnover intention. The effect of transformational leadership on turnover before being mediated was found to be insignificant with an original sample value of -.090 and p values (.216 > .05).…”
Section: Organizational Commitment To Turnover Intentioncontrasting
confidence: 76%